2007
DOI: 10.1038/sj.jid.5700786
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte–Fibroblast Interactions in Wound Healing

Abstract: Cutaneous tissue repair aims at restoring the barrier function of the skin. To achieve this, defects need to be replaced by granulation tissue to form new connective tissue, and epithelial wound closure is required to restore the physical barrier. Different wound-healing phases are recognized, starting with an inflammation-dominated early phase giving way to granulation tissue build-up and scar remodeling after epithelial wound closure has been achieved. In the granulation tissue, mesenchymal cells are maximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
854
1
28

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 1,101 publications
(903 citation statements)
references
References 114 publications
20
854
1
28
Order By: Relevance
“…Stressed or dying keratinocytes commonly release IL-1a, a cytokine that stimulates production of keratinocyte mitogens by stromal cells 28,29 . To determine a possible role of such paracrineacting growth factors in the hyperproliferation induced by Aldara treatment, we demonstrated upregulation of IL-1a mRNA levels 24 h after one topical Aldara treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stressed or dying keratinocytes commonly release IL-1a, a cytokine that stimulates production of keratinocyte mitogens by stromal cells 28,29 . To determine a possible role of such paracrineacting growth factors in the hyperproliferation induced by Aldara treatment, we demonstrated upregulation of IL-1a mRNA levels 24 h after one topical Aldara treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that Aldara also activated the NLRP-1 inflammasome in (human) keratinocytes resulting in caspase-1-dependent production of biologically active IL-1b. In addition, Aldara induces expression of G-CSF production by fibroblasts and the induction of S100A8/A9 28,29 and IL-23 production by dermal myeloid cells, which in turn induces IL-17 secretion by dermal gd-T cells 8 . IL-17 and G-CSF have an impact on keratinocytes resulting in their proliferation, whereas S100A8/A9 and CXCL1 are strong chemoattractants for neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…The hemidesmosomes in healing epithelia resemble C. elegans fibrous organelles in many ways. They are connected to the ECM underlying contracting myofibroblasts, and they undergo a dynamic reorganization process during epidermal cell migration and wound healing (Goldfinger et al, 1999;Werner et al, 2007). If the membrane receptor integrin level is aberrantly elevated, it will create unnecessary adhesion to the ECM and hamper cell migration.…”
Section: Control Of Hemidesmosome Component Levelsmentioning
confidence: 99%
“…In addition, it is beneficial to have both the keratinocytes and fibroblasts present, as the paracrine interactions between these two cell types are also very important to F o r P e e r R e v i e w effective healing [13,14]. When co-cultures of these cells are used, however, it is important to mitotically inhibit the fibroblasts to prevent over-growth of the culture.…”
Section: Introductionmentioning
confidence: 99%